ChemInform Abstract: Eaton′s Reagent‐Mediated Domino π‐Cationic Arylations of Aromatic Carboxylic Acids to Iasi‐Red Polymethoxylated Polycyclic Aromatic Hydrocarbons: Products with Unprecedented Biological Activities as Tubulin Polymerization Inhibitors. Issue 4 (January 2015) - Ghinet, Alina; Gautret, Philippe; Hijfte, Nathalie Van; Lede, Bertrand; Henichart, Jean‐Pierre; Bicu, Elena; Darbost, Ulrich; Rigo, Benoit; Daich, Adam
Abstract The π‐cationic arylation of methoxy substituted benzoic acids with reactive arenes [e.g. (II)] is developed to provide an optimized synthetic route to phenstatin (V).